Effect of chewing gum on the postoperative recovery of gastrointestinal function - Ge, Wei (Int J Clin Exp Med, 2015)
Postoperative gastrointestinal dysfunction remains a source of morbidity and the major determinant of length of stay after abdominal operation. There are many different reasons for postoperative gastrointestinal dysfunction such as stress response, perioperative interventions, bowel manipulation and so on. The mechanism of enhanced recovery from postoperative gastrointestinal dysfunction with the help of chewing gum is believed to be the cephalic-vagal stimulation of digestion which increases the promotability of neural and humoral factors that act on different parts of the gastrointestinal tract. Recently, there were a series of randomized controlled trials to confirm the role of chewing gum in the recovery of gastrointestinal function. The results suggested that chewing gum enhanced early recovery of bowel function following abdominal surgery expect the gastrointestinal surgery. However, the effect of chewing gum in gastrointestinal surgery was controversial.